The high king. - Alexander, Lloyd (New York, Holt, Rinehart and Winston, 1968)
In this fifth and final chronicle of Prydain the forces of good and evil meet in ultimate confrontation.
In dust jacket.
Keywords: Fairy tales; Fairy tales